Explore the soil factors driving soil microbial community and structure in Songnen alkaline salt degraded grassland - Bai, Zhenyin; Jia, Aomei; Li, Haixian; Wang, Mingjun; Qu, Shanmin (Frontiers in Plant Science, 2023)
Grassland saline-alkali degradation significantly affects plant community composition. However, the effects of different degradation stages on microbial community changes and soil quality remain unclear. Therefore, elucidating the effects of saline-alkali degradation on microbial community changes and soil quality is crucial for developing effective solutions to restore degraded grassland ecosystems. Three different stages were qualitatively selected in this study, namely the light degradation stage (LD), the moderate degradation stage (MD) and the severe degradation stage (SD). The results showed that saline-alkali degradation decreased the diversity of soil bacteria and fungi, and changed the composition of bacterial and fungal communities. With the deterioration of salinity in grassland, the relative abundance of Actinobacteriota and Chytridiomycota showed a decreasing trend. Sand, Clay, pH, EC, SOC, AN, TK and AK were the factors that affected the composition of soil bacteria community, Sand, Coarse silt, Clay, pH, EC, SOC, TN, AN, AP, TK and AK were the factors that affected the composition of soil fungi community. Different microorganisms are affected by different soil properties, and the changes of plant community and microenvironment are the main factors limiting the diversity and composition of soil microbial community. The revised minimum data set (RMDS) based on principal component analysis (PCA) was used to evaluate the grassland soil quality index (SQI) at different stages. The SQI showed a decreasing trend with the aggravation of grassland saline-alkali degradation. The results show that grassland saline-alkali degradation has a negative effect on microbial biodiversity and soil quality, so developing effective solutions to restore degraded grasslands is critical to maintaining biodiversity and ecosystem function.